Some "Pearls" on Medical Practice - Alfredo Darío Espinosa Brito (Centro Provincial de Información de Ciencias Médicas. Cienfuegos, 2015)
At a time like this, marked by incredible scientific and technological advances, many doctors also feel the need to share and write about their experiences, not strictly in academic terms, but using a narrative register more related to human interactions. This paper presents a group of phrases and comments, considered as "clinical pearls", which I have heard or learned during a long medical practice in direct contact with many colleagues in different places. It briefly and coherently compiles knowledge or tips for carrying out this profession and can be useful to others, especially, the young.